Design of Integrated Bioimpedance Analysis and Body Mass Index for Users with Special Needs - Ganjar Winasis; Munawar Riyadi; Teguh Prakoso (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
This research was conducted with the aim to build integration between Bioimpedance Analysis (BIA) and Body Mass Index (BMI) for users with special needs. The proposed system can measure height, weight, BMI and body composition simultaneously to be used by the elderly population and handicapped users. The proposed system is developed as a chair equipped with several system blocks, namely BIA block, BMI block, power supply block, and microcontroller block. Before starting the measurement, users only need to enter their age and gender data. The whole system is controlled by using Arduino Mega 2560 on the microcontroller block equipped with keypad for data input and an LCD to display measurement results. System testing is performed by comparing the measurement results with Omron HBF-375. The test involved 8 volunteers (4 males and 4 females). The test results show that the integrated BIA-BMI works well with an average error of 1.5%.